Tricks of the light essays on art and spectacle - Crary, Jonathan 1951- (Zone Books, 2023)
"This book features essays on modern and contemporary art and media systems"--
Keywords: Geschichte; Medien; Fernsehsendung; Kunst; Arts and society / History / 20th century; Arts and society / History / 21st century; Arts et société / Histoire / 20e siècle; Arts et société / Histoire / 21e siècle; SOCIAL SCIENCE / General; Arts and society; 1900-2099; History; Aufsatzsammlung